2016
DOI: 10.1007/s10995-016-2029-6
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study to Understand Nativity Differences in Breastfeeding Behaviors Among Middle-Class African American and African-Born Women

Abstract: Objective To explore nativity differences and the role of attitudes, social norms, and behavioral control perceptions surrounding breastfeeding initiation and duration among middle-class African-American (AA) and African-born (AB) mothers in the US. Methods Semi-structured individual interviews were conducted with 20 middle-class AA and AB mothers in central Ohio from December 2012 to February 2013. Interview questions were developed based on the Theory of Planned Behavior (TPB). Interviews were analyzed for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Qualitative work by Fabiyi et al identified different normative referents for breastfeeding: whereas African American women recalled bottle feeding and formula feeding during their youth, African women recalled more memories of breastfeeding . Additionally, the latter group reported more support from family members to continue breastfeeding and to breastfeed exclusively . Maternal perception that the infant is not satisfied by breastmilk is a common concern, and this study suggests that counseling should consider women's nativity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Qualitative work by Fabiyi et al identified different normative referents for breastfeeding: whereas African American women recalled bottle feeding and formula feeding during their youth, African women recalled more memories of breastfeeding . Additionally, the latter group reported more support from family members to continue breastfeeding and to breastfeed exclusively . Maternal perception that the infant is not satisfied by breastmilk is a common concern, and this study suggests that counseling should consider women's nativity.…”
Section: Discussionmentioning
confidence: 72%
“…Less is known about black women, particularly African‐born women, who compose a growing proportion of the population in the United States . Qualitative work by Fabiyi et al identified different normative referents for breastfeeding: whereas African American women recalled bottle feeding and formula feeding during their youth, African women recalled more memories of breastfeeding . Additionally, the latter group reported more support from family members to continue breastfeeding and to breastfeed exclusively .…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of the included studies were qualitative (Castaldo, Mirisola, Costanzo, & Marrone, ; Fabiyi, Peacock, Hebert‐Beirne, & Handler, ; Gallegos et al, ; Hill, Hunt, & Hyrkäs, ; Hufton & Raven, ; Ingram, Cann, Peacock, & Potter, ; Kolanen, Valimaki, & Vehvilainen‐Julkunen, ; Steinman et al, ; Textor et al, ; Twamley et al, ; Tyler et al, ; Wandel et al, ), and 23 were quantitative studies (Brick & Nolan, ; Bulk‐Bunschoten, Pasker‐de Jong, van Wouwe, & de Groot, ; Busck‐Rasmussen, Villadsen, Norsker, Mortensen, & Andersen, ; de Hoog, van Eijsden, Stronks, Gemke, & Vrijkotte, ; Dennis et al, ; Farchi, Asole, Chapin, & Di Lallo, ; Fawzi et al, ; Goel, House, & Shanks, ; Grewal, Andersen, Sellen, Mosdol, & Torheim, ; Griffiths, Tate, & Dezateux, , ; Jones & Belsey, ; Kelly, Watt, & Nazroo, ; Meftuh, Tapsoba, & Lamounier, ; Merewood et al, ; Moore, Nanthagopan, Hammond, Milligan, & Goff, ; Neault et al, ; Nolan & Layte, ; Parker et al, ; Rio et al, ; Rubin, Inbar, & Rishpon, ; Treuherz, Cullinan, & Saunders, ; Wallby & Hjern, ). Ten studies were conducted in the United Kingdom (Goel et al, ; Griffiths et al, , ; Hufton & Raven, ; Ingram et al, ; Jones & Belsey, ; Kelly et al, ; Moore et al, ; Treuherz et al, ; Twamley et al, ); eight in the United States (Fabiyi et al, ; Hill et al, ; Meftuh et al, ; Merewood et al, ; Neault et al, ; Parker et al, ; Steinman et al, ; Textor et al, ); three in Australia (Gallegos et al, ; Tyler et al, ); two each ...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the participants under study were immigrant mothers from Somalia (Grewal et al, ; Hill et al, ; Ingram et al, ; Kolanen et al, ; Steinman et al, ; Textor et al, ; Wandel et al, ), Ethiopia (Meftuh et al, ; Rubin et al, ), and Morocco (Bulk‐Bunschoten et al, ; Busck‐Rasmussen et al, ; de Hoog et al, ). One study included African mothers from Burundi, Congo, Liberia, and Sierra Leone (Gallegos et al, ), whereas other studies (Brick & Nolan, ; Castaldo et al, ; Dennis et al, ; Fabiyi et al, ; Farchi et al, ; Fawzi et al, ; Goel et al, ; Griffiths et al, , ; Hufton & Raven, ; Jones & Belsey, ; Kelly et al, ; Merewood et al, ; Moore et al, ; Neault et al, ; Nolan & Layte, ; Parker et al, ; Rio et al, ; Treuherz et al, ; Twamley et al, ; Wallby & Hjern, ) described the study population as Africans or Black Africans, without specifying which African country the mothers included in the study originated from.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation